Pengaruh Rasio Keuangan pada Kebiajakan Dividend dalam Perusahaan Perbankan dengan Firm Size sebagai Variable Moderasi - Adam Putra Oka; Ade Widiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Indonesia's increasing economic growth has intensified competition in the business world, particularly in the Indonesian banking sector, from conventional to sharia-compliant. Furthermore, the entry of foreign banks has made business activities in Indonesia increasingly complex. The stock market is a crucial source of funding for companies. Publicly listed companies can increase their funding sources by selling ownership in the capital market. Dividends are the distribution of company earnings to shareholders in the form of cash, assets, or other forms. Dividend policy is a policy for sharing company profits with shareholders, which is announced in the form of dividends and retained earnings for the benefit of company growth. The proportion of dividends distributed to shareholders depends on the company's profitability and dividend policy. The percentage of profits distributed to shareholders in the form of dividends is called the Dividend Payout Ratio.Differences in calculations in determining financial ratios in banking companies are an interesting focus in this study. The study results show quite significant results between financial ratios and managers' decisions in making dividend policy decisions. In the future, the results of this study are expected to be a consideration and reference for investors who want to enter the world of investment, especially in the banking sector.